Pengaruh Posisi Pengelasan Dan Diameter Filler Pada Hasil Pengelasan Daun Propeller Dengan Gas Metal Arc Welding - Dwisetiono Dwisetiono; Rizal Dikrulloh (Departemen Teknik Kelautan Universitas Hasanuddin, 2022)
The propeller is a key component in ship propulsion as a means of producing thrust to move the ship. The damage that occurs to the propeller on the propeller leaf is fouling, erosion occurs due to cavitation, cracks and bends occur due to collision. This research was conducted to analyze the effect of welding position and filler diameter on the results of welding repair of propeller leaf with GMAW. The tests carried out are tensile tests, hardness tests, impact tests and macrographic observations. Tensile test results on GMAW welding for maximum tensile strength at the 2G welding position have a high ultimate tensile strength value. In the 1G and 2G welding positions the macrographic observations were good because there were no welding defects found compared to the 3G welding position. The highest hardness results in 1G welding compared to 2G and 3G welding positions. The result of the highest impact test is the 1G welding position compared to the 2G and 3G welding positions. Based on the results of testing the difference in filler diameter, defects were found in the test samples at the position of 2G filler 1.2 mm, 3G filler 1.0 mm, and 3G filler 1.2 mm, while the position of 1G filler 1.0 mm, 1G filler 1.2 mm, and 2G 1.0 mm filler found no defects. For the tensile test, the hardness and impact on the 1.0 mm filler diameter have a high average value compared to the 1.2 mm filler diameter.